SCENIC SOURCES OF SEMANTICS OF LITERARY TELEVISION THEATER OF THE 1960-1980TH / Сценические истоки семантики литературного телетеатра 1960–1980-х годов - ROSTOVA N.V. / РОСТОВА Н.В. (Наука телевидения, 2017)
The author tries to determine artistic features and sources of television theater, regretting that it ceased to exist on national TV, though it used to be a very serious emotional and intellectual part of life of people in our country. In 1960–1980th television theater was a significant experimental base for actors and directors. A unique television genre just started to develop, to find means of expression, a special television language was developed in creative search. It was special, because a television theater is not a theater, but also not a cinema. According to the author, it is a kind of a very esthetic “corridor”, an unusual form of fiction interesting from all points of view: both visual, and semantic, and as a way of existence of an actor on the screen. Disappearance of television theater at any stage of reforming of national television wasn’t connected with its degeneration or natural death in any way. Transient disappearance of literature and theater from the screen breached art, barbarously lopping off the cultural root, and the precious experience which had been accumulated by founders was lost, connection between generations was destroyed. The author considers that the literary television theater had scenic sources, namely the well-known performance “The Brothers Karamazov” staged in Art theater in 1910 by V. Nemirovich-Danchenko, which became an important stage, “the whole era” in the creative search of the theater. An absolutely new scenic form of a narration was offered in it, where the usual theatrical conventions were violated, the purposes, obligatory for comprehension of theatricality and literary frame were overcome, and the prerequisites created for future television theater with the similar division of the script into unequal episodes became a specific feature of telework were created. The esthetic methods of transposing of a literary work on stage opened by Nemirovich-Danchenko: lack of external action, movement in its pre-Chekhov understanding; unlimited time of performing of classical prose; non-obligation of splitting the action on acts, identical on time; acceptability of long monologues; inclusion the reader into the action; combination of action fragments with verbal descriptions; visual manifestation of a narration structure in a hint, a detail, plasticity, i.e. really conditional receptions, appeared to be absolutely natural to the television theater and became the basis for detection of its specifics.